Quality of service, tax outreach, and online payment systems: do they affect taxpayer compliance with land and building taxes (PBB) in the Regional Revenue Agency in the central region of Bandung City? - Refiyani, Mega; Apriliana, Tria (Universitas Wiralodra, 2023)
The study's objective was to examine how customer satisfaction, tax socialization, and online payment methods affected taxpayer compliance at Bapenda in Bandung City's Central Region. By distributing questionnaires based on the variables being measured, this study adopts a quantitative methodology. 100 taxpayers from Bandung City Bapenda's Central Region served as the study's sample. The SPSS 25.0 version is used to process the collected data. Additionally, descriptive analysis, the traditional assumption test, multiple linear regression analysis, and the coefficient of determination test were all used in the data analysis for this study. According to the study's findings, online payment methods, tax socialization, and service quality all have a favorable and considerable simultaneous impact on taxpayer compliance.